(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Research on the effectiveness of volleyball training in the development of reaction speed and movement coordination in cadets. The study involved 60 cadets, who were distributed to experimental and control groups. The experimental team conducted volleyball sessions 3 times a week, for 90 minutes each. Reaction speed and motion compatibility were evaluated through tests. In the experimental group, the reaction rate increased by +18 %, action compliance by +20%; while in the control group, an increase of +6% and +5% was recorded. Volleyball training has a high pedagogical potential in the effective development of psychomotor skills and Comanche skills in cadets.